THE EFFECT OF PROMOTION COST AND DISTRIBUTION COST ON COMPANY’S SALES OF THE FAST MOVING CONSUMER GOODS INDUSTRIES - Sinta Wardani; Ujang Sumarwan; Tb. Nur Ahmad Maulana (Journal of Economics, Business, and Accountancy Ventura, 2013)
The purposes of this study are (1) to analyze the effect of the promotion cost and distribution cost on company’s sales partially and simultaneously (2) to formulate managerial implications related to the results of this study. Data was collected from 29 companies which separated into 18 foreign direct investments companies and 11 domestic investment’s companies. Secondary data was gathered through consolidated financial statements’ companies which listed on IDX for the 2007-2012 years ended. Data panel analysis fixed effect model was used to estimate the effects of promotion cost and distribution cost. Based on the FEM analysis, all independent variables of foreign direct investment and domestic investment companies has significant effect on their sales. The results of this study suggestedfor managerial implications to increase the efficiency of promotion cost and distribution cost.